2020
DOI: 10.1101/2020.06.05.135699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 proteases cleave IRF3 and critical modulators of inflammatory pathways (NLRP12 and TAB1): implications for disease presentation across species and the search for reservoir hosts

Abstract: The genome of SARS-CoV-2 (SARS2) encodes for two viral proteases (NSP3/ papain-like protease and NSP5/ 3C-like protease or major protease) that are responsible for cleaving viral polyproteins for successful replication. NSP3 and NSP5 of SARS-CoV (SARS1) are known interferon antagonists. Here, we examined whether the protease function of SARS2 NSP3 and NSP5 target proteins involved in the host innate immune response. We designed a fluorescent based cleavage assay to rapidly screen the protease activity of NSP3 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 108 publications
2
33
0
Order By: Relevance
“…Many of these screens have used a cell-free system involving purified enzyme and Förster resonance energy transfer (FRET)-based reporters. 16 While these studies have identified different potential inhibitors, they have a crucial drawback: cytotoxicity. By beginning our screen with a cell-based system, we sought to identify compounds that inhibit PLpro but cause minimal cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these screens have used a cell-free system involving purified enzyme and Förster resonance energy transfer (FRET)-based reporters. 16 While these studies have identified different potential inhibitors, they have a crucial drawback: cytotoxicity. By beginning our screen with a cell-based system, we sought to identify compounds that inhibit PLpro but cause minimal cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we identified the SARS-CoV-2 PL pro cleavage site of ULK1 after glycine (G) 499, follows precisely the consensus sequence recognized by the deubiquitinase. The interferon regulatory factor 3 (IRF3) was also recently reported as a substrate of PL pro following an LGGG consensus motif similar to ULK1 (32). The targeting of ULK1 and possibly other host proteins harboring an LXGG motif therefore underscores potentially a novel mechanism through which betacoronaviruses subvert cellular autophagy.…”
Section: Ulk1 Plays a Dual Role In Mcov Replicationmentioning
confidence: 99%
“…Moreover, Dikic and coworkers showed that SARS-CoV-2 nsp3-PLpro limited IFN-I production by cleaving the ubiquitin-like protein ISG15 and decreasing the phosphorylated IRF3 (Shin and others 2020 ). Furthermore, Moustaqil and others ( 2020 ) employed a cell-free cleavage assay to show that SARS-CoV-2 nsp3 was able to directly cleave IRF3, resulting in decreased IRF3 activation and IFN-I production.…”
Section: Nonstructural Proteinsmentioning
confidence: 99%